Statistical Correlation on Internal Issues of Garment Textile industry in Pakistan - Memon, Mohammad Salih; Sattar Shah, Abdul; Ali Khowaja, Imdad; Munir Ahmadani, Muhammad (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
This research investigates the Statistical Correlation on Internal Issues of Spinning Textile industry in Pakistan.Data were collected from various primary as well as secondary sources. It was revealed that after performing Pareto analysis the output shows total counts equivalent to 1853. As it is suggested to take about 80% to solve the overall issues but here the 80% is between 7th and 8th issue. Therefore it is decided to take about 75% through which 7 issues may be selected as shown in the Pareto chart 6-8. However 8 issues are equal to 1482 which is about 84%. Government of Pakistan should formulate the policy that above issues can be resolve.